2011
DOI: 10.1155/2011/525691
|View full text |Cite
|
Sign up to set email alerts
|

CCL5/RANTES Gene Polymorphisms in Slavonic Patients with Myocardial Infarction

Abstract: Coronary artery inflammation is a critical process in the pathogenesis of myocardial infarction (MI). The chemokine CCL5/RANTES (regulated upon activation, normal T cells expressed and secreted) is expressed in advanced atherosclerotic lesions. Functional polymorphisms of the RANTES gene can, therefore, be involved in the pathogenesis of coronary artery disease. We examined the association of polymorphisms in the RANTES gene with myocardial infarction in Slavonic populations of Czech and Russian origin. A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…However, an observational study in Korea have inconsistently shown a decreased risk of CAD in individuals with G-403A polymorphism [11]. Still other studies could not draw any firm conclusion about the existence of association between G-403A polymorphism and CAD because of the limitation in sample size [12][14]. We therefore performed a meta analysis of available studies with a case-control or cohort design to clarify the role of the G-403A polymorphism in RANTES gene in development of CAD.…”
Section: Introductionmentioning
confidence: 99%
“…However, an observational study in Korea have inconsistently shown a decreased risk of CAD in individuals with G-403A polymorphism [11]. Still other studies could not draw any firm conclusion about the existence of association between G-403A polymorphism and CAD because of the limitation in sample size [12][14]. We therefore performed a meta analysis of available studies with a case-control or cohort design to clarify the role of the G-403A polymorphism in RANTES gene in development of CAD.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, Jang et al (2007) have suggested that the -403A allele was associated with lower serum RANTES concentration and described the significant protective effect of the polymorphism on CAD risk in Korean male patients with or without type 2 diabetes (Jang et al, 2007). Most of the studies in this meta-analysis showed no relationship between the polymorphism and CAD risk (Szalai et al, 2001;Park et al, 2007;Vogiatzi et al, 2009;Shi Ying et al, 2010;Tavakkoly-Bazzaz, et al, 2011;Tereshchenko et al, 2011).…”
Section: Discussionmentioning
confidence: 77%
“…However in another study in Korean male population RANTES −403 A allele was associated with reduced risk of CAD but they did not find such association in patients taking lipid-lowering medicine (Jang et al, 2007). A more recent study in Slavonic patients also found no association between RANTES −403 polymorphism and MI (Tereshchenko et al, 2011).…”
Section: Discussionmentioning
confidence: 86%